Geographical principles of grouping toponyms of Zhambyl region (Kazakhstan) (ҚазҰУ Хабаршысы. География сериясы, 2024)
The article analyzes scientific approaches to geographical principles of grouping toponyms. The study's relevance is due to the lack of work on the toponymy of Southern Kazakhstan and the need to develop this direction in Kazakh science. The purpose of the study was to build a classification of toponyms of the Zhambyl region based on geographical principles.The research methodology contains the following stages of the development of geographical principles of grouping toponyms of the Zhambyl region: 1) selection of geographical names (toponyms important for the region in historical, cultural, geographical, and political aspects) and a brief description of the largest geographical objects; 2) processing of the results of the analysis of toponyms; 3) building a system of geographical principles of grouping toponyms; 4) systematization and identification of patterns of toponyms of the region. During the primary classification, two groups of toponyms were identified: geographical names related to localities and geographical names related to natural formations. Three principles of grouping toponyms of the Zhambyl region symbolizing the region in the consciousness of the Kazakh society are used: normative-legal, historical-geographical, and cultural-linguistic principles. Practical significance of the study: the toponymic classification of the main geographical names of the Zhambyl region has been compiled: 1) natural geographical names; 2) cultural and historical geographical names; 3) geographical names associated with the names and surnames of people. It was found that the main part of the toponyms of the region comes from the Turkic, Persian, Altaic, or Arabic languages. By the beginning of the XXI century, many administrative-territorial units received names in the Kazakh language. Most of the toponyms were formed from the names of natural geographical objects (mainly from the names of rivers), a small part belongs to the topographic group associated with the names and surnames of people.